2013
DOI: 10.1093/cercor/bht215
|View full text |Cite
|
Sign up to set email alerts
|

Differential Modifications of Synaptic Weights During Odor Rule Learning: Dynamics of Interaction Between the Piriform Cortex with Lower and Higher Brain Areas

Abstract: Learning of a complex olfactory discrimination (OD) task results in acquisition of rule learning after prolonged training. Previously, we demonstrated enhanced synaptic connectivity between the piriform cortex (PC) and its ascending and descending inputs from the olfactory bulb (OB) and orbitofrontal cortex (OFC) following OD rule learning. Here, using recordings of evoked field postsynaptic potentials in behaving animals, we examined the dynamics by which these synaptic pathways are modified during rule acqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 74 publications
(97 reference statements)
3
27
0
Order By: Relevance
“…Furthermore, olfactory rule learning also induces a transient period of heighten piriform cortical excitability (Saar & Barkai, ), as well as a transient differential modification of ascending and descending inputs to the PCX (Cohen et al . ) that recovers within days of the initial learning. By contrast, the right aPCX showed more stable beta and theta frequency changes after learning.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Furthermore, olfactory rule learning also induces a transient period of heighten piriform cortical excitability (Saar & Barkai, ), as well as a transient differential modification of ascending and descending inputs to the PCX (Cohen et al . ) that recovers within days of the initial learning. By contrast, the right aPCX showed more stable beta and theta frequency changes after learning.…”
Section: Discussionmentioning
confidence: 88%
“…; Martin & Ravel, ; Cohen et al . ). Why these effects occur with different temporal dynamics in the two hemispheres during learning, resulting in aPCX asymmetry, remains unclear.…”
Section: Discussionmentioning
confidence: 97%
“…Thus, as odors acquire or change associative value through experience or training, the OFC may provide top-down feedback on stimulus-predicted outcomes. In fact, recent evidence has demonstrated that as animals learn difficult odor discriminations, there is a concomitant plasticity of OFC–piriform cortex top-down synaptic input, with a depression of left OFC input to left piriform cortex (Cohen et al, 2013). Once the discrimination is well learned, the strength of this connection returns to baseline levels.…”
Section: The Role Of the Olfactory Cortex In Odor Perceptionmentioning
confidence: 99%
“…In addition to this state dependence, the PCX-orbitofrontal cortex connection is also experience-dependent. In fact, Cohen, Wilson, and Barkai (2015) compared changes in synaptic input to the PCX from the olfactory bulb and from the orbitofrontal cortex during odor rule learning. Odor rule (or set) learning occurs when animals are trained on a difficult odor discrimination task.…”
Section: Extended Olfactory Networkmentioning
confidence: 99%
“…Odor rule learning results in a myriad of synaptic and biophysical changes within the PCX (Barkai, 2014; Saar, Reuveni, & Barkai, 2012), but also modifies synaptic connectivity between the PCX and some of its monosynaptic partners. Specifically, during acquisition of odor rule learning the olfactory bulb synaptic input to the PCX was potentiated, and simultaneously the orbitofrontal cortex input to the PCX was depressed [(Cohen, Wilson, et al, 2015); Fig. 1].…”
Section: Extended Olfactory Networkmentioning
confidence: 99%